A New Perspective for Predicting the Therapeutic Success of RFA in Solid BTNs: Quantitative Initial RFA Ratio by Contrast-Enhanced Ultrasound - Zhu, Yaqiong; Jiao, Ziyu; Zhu, Lianhua; Xie, Fang; Song, Qing; Yan, Lin; Luo, Yukun; Zhang, Mingbo (Frontiers in Endocrinology, 2022)
Objective The short-term therapeutic success of radiofrequency ablation (RFA) in solid benign thyroid nodules is of great concern. The aim of this study was to investigate a new method, initial radiofrequency ablative ratio (IRAR) using contrast-enhanced ultrasound (CEUS), for predicting therapeutic success of RFA in solid benign thyroid nodules (BTNs) immediately and effectively after RFA. Methods A total of 813 nodules in 776 patients with benign thyroid nodules were treated with RFA from January 2014 to August 2018, among which 120 patients (M:F=41:79) with 120 solid BTNs (small: ≤10ml, n=57; medium: 10-30ml, n=42; large: >30ml, n=21) were enrolled in our study according to the inclusion criteria. The IRAR was defined as the ablative volume ratio immediately after RFA displayed by CEUS. The therapeutic success was evaluated at the 6-month follow-up. The relationship between the IRAR and volume reduction ratio (VRR) at 6-month was analyzed. The marginal regrowth of solid BTNs was also examined by CEUS at the 6 and 12 months of follow-up. Results In medium and large nodules, the IRAR was significantly and positively correlated with VRR (r= 0.69, P < 0.001) at 6 months after RFA. There was a tendency to achieve therapeutic success (50% VRR: 55/63, 87.3%) when the IRAR exceeded 75%, and marginal regrowth was also relatively slow within 12 months after a single session treatment. No significant correlation between IRAR and VRR of small nodules was found. In conclusion, IRAR is significantly and positively correlated with VRR, which may indicate therapeutic success when it exceeds 75%. Conclusions CEUS can be used to accurately quantify the IRAR, which is positively correlated with the VRR. Moreover, the IRAR may be used as a parameter to predict the short-term therapeutic success of RFA in solid BTNs.